Consumer preferences for certified wines in France: A comparison of sustainable labels - Adeline Alonso Ugaglia; Britta Niklas; Wolfram Rinke; Dan Moscovici; Jeff Gow; Lionel Valenzuela; Radu Mihailescu (Wine Economics and Policy, 2021)
The wine industry has faced various environmental and social challenges. On the demand side, consumer demand for sustainable wines has been increasing but, to date, it is unknown whether consumers perceive wine companies' efforts to obtain sustainable development (SD) certifications and labels as being valuable or how they differentiate them. On the supply side, sustainable wine production is increasing but producers report a lack of information to engage and select their SD strategy. This article uses a logistic regression and an artificial neural network model to show how French consumers differentiate and value different SD labels (Organic, Biodynamic, Sustainable, Fairtrade, Natural). Results show that consumers' willingness to buy and willingness to pay are influenced by the importance each consumer gives to the certification. For all other drivers, consumers differentiate between labels, highlighting the importance of comparison between and knowledge about each of them, thereby aiding producers in choosing an appropriate marketing strategy.
Keywords: 330; Consumer preferences; stated preferences; wine; certified wines